Fenomena Pengemis Virtual Di Tiktok Dikaji Dari Teori Etika Kekristenan, Pendidikan Karakter Dan Literasi Digital - Wewengkang, Ervino Jenrico Nicolas; Kuwissy, Gaby Juliana; Wohon, Frimsi; Tolego, Yopi Baleona; Palempung, Franty F (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
The phenomenon of virtual beggars on Tiktok has sparked debates in society, particularly regarding ethics, moral values, and digital literacy. This study examines the phenomenon from the perspectives of Christian Ethics, character education, and digital literacy. Using qualitative methods, a phenomenological approach, and literature review, the research explores how virtual beggars employ emotional narratives to attract viewers' attention and donations. Within Christian Ethics, such actions raise moral dilemmas as they may exploit empathy dishonestly. Simultaneously, character education is crucial in equipping young generations with strong moral values to critically evaluate actions. Digital literacy also plays a significant role in helping society recognize manipulative content and make informed decisions in digital interactions. This study underscores the need for a holistic approach that integrates ethics, character education, and digital literacy to address the negative impacts of this phenomenon while fostering a more empathetic, responsible, and ethical society in the digital era.